Crystal structure of (E)-3-(3-methoxybenzylidene)benzofuran-2(3H)-one, C16H12O3 - Zheng Liang Liang; Liu Xiong Li; Dong Zhang Chao; Shi Yang; Pan Bo Wen; Feng Ting Ting (Zeitschrift für Kristallographie - New Crystal Structures)
C16H12O3, monoclinic, P21/c (no. 14), a = 10.9636(14) Å, b = 12.1767(12) Å, c = 10.1557(13) Å, β = 116.588(16)°, V = 1212.4(3) Å3, Z = 4, Rgt (F) = 0.0366, wR ref(F 2) = 0.1019, T = 250.00(10) K.